Strategi Pemasaran Berbasis Selfie Untuk Meningkatkan Daya Saing UMKM di Kecamatan Pondok Aren Kota Tangsel - Hindardjo, Anton; Ferranti, Putri Andari; Pramudena, Sri Marti; Marlapa, Eri (Jurnal Pengabdian Masyarakat Singa Podium (JPMSIPO), 2024)
This case study investigates the adoption of selfie-based marketing strategies by Micro, Small, and Medium Enterprises (MSMEs) in the District Pondok Aren, South Tangerang City. The research primarily focuses on the utilization of selfies as branding tools, the personalization of content through Augmented Reality (AR) technology, and the safeguarding of consumer data security. Contrary to viewing selfies merely as a trend, this study identifies them as a crucial element in establishing a robust brand image. The integration of consumer selfies serves as a key strategy for extending consumer identities into the digital sphere, fostering deeper engagement between consumers and brands and cultivating an ongoing emotional connection. AR technology enhances content personalization, enabling consumers to interact with brands via customized facial filters, thereby making the consumer experience more distinctive and relevant. Consumer data security emerges as a vital aspect, underscored by protective measures and transparency to ensure a safe and comfortable interaction environment. By focusing on innovation and aligning with digital marketing trends, this strategy offers practical guidance for MSMEs in the District Pondok Aren.